ANALISIS KONSEPTUAL POTENSI ZENO’S PARADOX SEBAGAI SARANA PENGUATAN INTUISI SISWA DALAM MEMAHAMI LIMIT DAN DERET TAK HINGGA - Subhan, Fiqri; Harahap, Dwita Meliani; Sinaga, Petra Aprina Benedicta; Sinurat, Relly; Pane, Sally Yunita Mutiara (De Fermat : Jurnal Pendidikan Matematika, 2026)
The concept of limits and infinity is a fundamental foundation in advanced mathematics; however, it often creates conceptual difficulties for students due to its abstract nature. One approach that can be used to strengthen students’ conceptual understanding is through the use of Zeno’s Paradox. This paradox describes the problem of motion through the division of distance that continues indefinitely, making it closely related to the concepts of limits and infinite series in calculus. This study aims to conceptually analyze the potential of the Zeno Paradox in strengthening students’ mathematical intuition regarding the concepts of limits and infinity in mathematics learning. The research employed a qualitative approach using a literature study (library research) method. Data were obtained from various scientific journal articles, conference proceedings, and books relevant to the concepts of limits, infinity, mathematical intuition, and Zeno’s paradox in mathematics education. Data analysis was conducted using content analysis techniques, including data reduction, categorization, conceptual analysis, and conclusion drawing. The results of the study indicate that Zeno’s Paradox has pedagogical potential as a means to generate cognitive conflict that can strengthen students’ mathematical intuition in understanding the concepts of limits and infinity. Through paradox illustrations, students can understand that processes that occur without bound do not always produce infinite values but can approach a particular value. Therefore, the Zeno Paradox can serve as an alternative approach in mathematics learning to strengthen students’ conceptual understanding of limit concepts.